ISMAIL MUNDU TO-PANRITA AS A SCHOLAR AND MUFTI OF THE KUBU KINGDOM IN WEST KALIMANTAN - Patmawati; Hesty Nurrahmi; Fitri Susanti Ilyas (Jurnal Dakwah Tabligh, 2022)
This research aimed to reveal the role of the local scholars in the spread of Islam in Borneo. The only famous cleric in Borneo is Muhammad Arsyad al-Banjari from South Kalimantan. Each region in Kalimantan has its scholars, the local cleric of West Kalimantan who will be discussed in this paper is Ismail Mundu to-panrita (a scholar, religious leader, and knowledgeable person, who has worked for the benefit of the community), as a cleric and mufti of the Kubu Kingdom. The research method used in this study was the historical method by taking the following steps, namely: heuristics, criticism, auffassung, and desterliung. The results of the study found that Ismail Mundu as a scholar had practiced his knowledge in educating the community and creating a religious and peaceful society. He was appointed to be the Mufti of the Kubu Kingdom due to his success in eradicating ignorance in the community. After the Kubu Kingdom ended and merged with the Republic of Indonesia, Ismail Mundu was elected to be a judge of the Kubu Court. Ismail Mundu as mufti gave fatwas and explanations to the public regarding religious issues, which can be seen in his various works, including interpretations of the holy book Al-Quran in Bugis translation, collections of Isra' mi'raj stories, collections of sermons, collections of wirid, Remembrance of Tauhidiyah, Mukhtasar al-Mannan 'ala al-'Aqidat al-Rahman, Book of Mukhtasar Aqaid, Faidah Istighfar Rajab, Schedule of Al-Nikah, Majmu' al-Mirats fi hukmi al-Faraid. The classification of Ismail Mundu's works includes interpretation, monotheism, tasawuf, fiqh, and history.